Leading for Success : Unleash Your Leadership Potential to Achieve Extraordinary Results. - Cook, Sarah, 1955- (Soft skills for IT professionals., 2009)
Leading for Success is intended to provide IT managers with practical advice and tips on how to become an effective leader. Whatever the environment in which you work, providing effective leadership fosters a climate where team members want to give of their best and where organisational goals are more likely to be reached. Furthermore, there is a strong focus on leadership and the creation of stakeholder value for an organisation.